Characteristics Biobriquettes from Mushroom Baglog Waste Carbonization Production - Novel Karaman; Ika Nawang Puspitawati; Kindriari Nurma Wahyusi; Sintha Soraya Santi; Suprihatin; Erwan Adi Saputro (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
Bio briquette is a briquette based on agricultural waste because it is deliberately made from biomass charcoal. The utilization of agricultural waste such as mushroom planting media to be processed as bio briquette requires a very cheap cost. Bio briquettes that are processed properly and correctly, will produce high-quality briquettes. The purpose of this study was to produce a biobriquette from baglog mushroom waste and to determine the characteristics of the biobriquette. The research material used consisted of 400 grams of mushroom baglog waste and 40 grams of starch as adhesive. The briquette dough is then printed cylindrical. The printed briquettes are then heated at 80°C for 5 hours to reduce the moisture content. The result of smoke test is the smoke will stop in 17 seconds with the color of the smoke is white. The Combustion of speed test, the results obtained are 0,0019 gram/second with an initial sample weight of 2, 4 grams and burning for 20 minutes 35 seconds with a final sample weight of 0,387 grams. The result of ash content is 0.16%. This result is in accordance with the SNI issued by our government. SNI of ash content is max 8 %.